2019
DOI: 10.1007/s11661-019-05235-8
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Thermomechanical Treatment and Nb Micro-alloying on the Hardenability of Ultra-High Strength Steels

Abstract: For the construction of mobile crane booms, ultra-high strength steels produced via thermomechanical processing (TMP) have widely substituted steels fabricated through the conventional quenching and tempering (Q+T) route. A strong deformation of the austenite grain during hot rolling followed by direct quenching (DQ) offers benefits in terms of strength and toughness. To guarantee an optimal through-hardening, alloying elements retarding the c to a transformation are used. To explore the influence of the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Combining Figures 8 and 9, it is found that the larger grain size of the test surface promotes the formation of martensite in the quenching process, resulting in a larger martensite fraction and higher hardness. Ahmed et al [30,31] also have reported that more refined grains are not conducive to martensite transformation, consistent with our finding. The grain size of sample A is large, the grain size distribution of each test surface is not uniform, so the microstructure of each test surface changes a lot, and the hardness fluctuates greatly, which is not conducive to the control of narrow hardenability bandwidth.…”
Section: Resultssupporting
confidence: 93%
“…Combining Figures 8 and 9, it is found that the larger grain size of the test surface promotes the formation of martensite in the quenching process, resulting in a larger martensite fraction and higher hardness. Ahmed et al [30,31] also have reported that more refined grains are not conducive to martensite transformation, consistent with our finding. The grain size of sample A is large, the grain size distribution of each test surface is not uniform, so the microstructure of each test surface changes a lot, and the hardness fluctuates greatly, which is not conducive to the control of narrow hardenability bandwidth.…”
Section: Resultssupporting
confidence: 93%